EPV 20. Vascular encephalopathy is a major risk factor for poor vestibular compensation. Issue 9 (September 2016) - Zwergal, A.; Schöberl, F.; Patzig, M.; Forbrig, R.; Brandt, T.; Dieterich, M.
Abstract : Background and aim: Acute unilateral vestibular loss leads to vertigo sensation, nystagmus and postural imbalance. As a rule, a behavioral recovery of the signs and symptoms follows over days to months due to central vestibular compensation (VC). The present study aimed to investigate the influence of cerebral vascular lesions on VC by following a large cohort of patients after vestibular neuritis. Methods: 235 patients (mean age: 54.2 ± 15.2, 53.4% men) with the clinical picture or history of an acute unilateral vestibulopathy, who were seen at the Department of Neurology and the German Center for Vertigo and Balance Disorders over the last 10 years, were included in the study. All patients underwent a detailed neuro-ophthalmological and neurological examination, including measures of the subjective visual vertical (SVV), ocular torsion (OT), head impulse test (HIT), provocation nystagmus (PN), visual acuity and postural control and were followed along their course of VC (mean number of visits 3.5 ± 1.2, mean time of follow-up 217 ± 625 days). In all patients a cranial MRI was available at onset of vestibular failure. The MRI was assessed by a two senior neuro-radiologist. Extent of supra- and infratentorial vascular white matter lesions was classified by the ARWMC scale (0–3 points). Strategic lesions in the vestibular network (medulla, vestibulocerebellum, thalamus) were registered separately. Patients were indicated as poorly compensated, if deviation of SVV (>2.5°), PN and postural asymmetry persisted for longer than 3 months after vestibular failure. Results: 13.3% of patients were classified as poorly compensated at 3 months (PN: 55%, SVV deviation: 36%, postural asymmetry: 22%), 12.8% at 6 months and 10.6% at 12 months after acute unilateral vestibulopathy. These patients had significantly higher ARWMC scales as compared to patients with regular VC ( p < 0.001). Supratentorial white matter lesions had the worst impact on VC. Among patients with poor VC 85% had supratentorial white matter lesions, 15% in the cerebellum. Strategic vascular lesion in the medulla or thalamus had only a minor impact on VC. Conclusions: About 10% of patients have an impeded course of VC after acute unilateral vestibulopathy. Supratentorial vascular encephalopathy is a major risk factor for poor VC and should be considered to guide the intensity of physical treatment following acute unilateral vestibulopathy.